Small RNA Sequencing Reveals Differential miRNA Expression in the Early Development of Broccoli (Brassica oleracea var. italica) Pollen - Li, Hui; Wang, Yu; Wu, Mei; Li, Lihong; Jin, Chuan; Zhang, Qingli; Chen, Chengbin; Song, Wenqin; Wang, Chunguo (Frontiers in Plant Science, 2017)
Pollen development is an important and complex biological process in the sexual reproduction of flowering plants. Although the cytological characteristics of pollen development are well defined, the regulation of its early stages remains largely unknown. In the present study, miRNAs were explored in the early development of broccoli (Brassica oleracea var. italica) pollen. A total of 333 known miRNAs that originated from 235 miRNA families were detected. Fifty-five novel miRNA candidates were identified. Sixty of the 333 known miRNAs and 49 of the 55 predicted novel miRNAs exhibited significantly differential expression profiling in the three distinct developmental stages of broccoli pollen. Among these differentially expressed miRNAs, miRNAs that would be involved in the developmental phase transition from uninucleate microspores to binucleate pollen grains or from binucleate to trinucleate pollen grains were identified. MiRNAs that showed significantly enriched expression in a specific early stage of broccoli pollen development were also observed. In addition, 552 targets for 127 known miRNAs and 69 targets for 40 predicted novel miRNAs were bioinformatically identified. Functional annotation and GO (Gene Ontology) analysis indicated that the putative miRNA targets showed significant enrichment in GO terms that were related to plant organ formation and morphogenesis. Some of enriched GO terms were detected for the targets directly involved in plant male reproduction development. These findings provided new insights into the functions of miRNA-mediated regulatory networks in broccoli pollen development.